Profesinė komunikacija teminiame bibliotekininkystės tinklaraštyje: atvejo analizė - Manžuch, Zinaida (Information & Media, 2010)
Straipsnyje aptariami naujos komunikacijos priemonės – teminių bibliotekininkystės tinklaraščių –naudojimo ypatumai profesinės komunikacijos kontekste. Lietuvoje atsiranda pirmieji tokio pobūdžio tinklaraščiai, tačiau trūksta empirinių šios srities tyrimų. Straipsnyje analizuojamas profesinės komunikacijos teminiame bibliotekininkystės tinklaraštyje „Rock&roll bibliotekininkas“ atvejis. Tyrimas naudingas vertinant tinklaraščių kaip komunikacijos priemonės potencialą bei atskleidžiant profesinės komunikacijos tendencijas. Atlikus tyrimą daromos išvados, kad tinklaraščio vartotojai tik iš dalies naudojasi šia priemone profesinės komunikacijos tikslais. Vartotojams aktualiausios profesinio tapatumo bei žinių, patirties dalijimosi sritys. Manoma, kad lėtą tinklaraščio adaptavimą profesinei komunikacijai nulemia naujos technologijos formuojama kitokia komunikacijos kultūra ir tai, kad tirtas pradinis tinklaraščio plėtros etapas. Pagrindiniai žodžiai: teminiai tinklaraščiai, bibliotekininkystė, atvejo analizė, profesinė komunikacija. Professional Communication in the Topical Librarianship Blog: A Case Study Zinaida Manžuch Summary The patterns of professional communication in the topical librarianship blog are explored in the paper. The huge impact of topical blogs on the development of professional communities, knowledge and experience sharing, and learning is widely aknowledged. Although the subject of topical blogs usage patterns has been analysed by library and information researchers wordwide, there haven’t been any attempts to perform similar empirical research in Lithuania. In most cases, available research worldwide tends to be descriptive and narrowly oriented at information sharing practices. The aim of the paper was to determine the patterns of blog usage for the professional communication purposes by analysing the case of the Rock&Roll Librarian blog. In order to overcome the limitations of previous research, the concept of professional communication was discussed and used as a guidance for interpreting findings of the empirical research. The research methodology was based on the analysis of features of blogs as a communication medium and different research approaches. The qualitative and quantitative content analysis of the blog texts and statistical usage data provided by Google Analytics was performed. The findings suggested that the blog only partly was used for professional communication purposes. Professional communication was not sufficiently visible at the initial stage of blog existence. However, the early patterns of professional communication, such as the focus on professional identity issues and knowledge sharing practices, emerged. Another notable blog usage tendency was the low activeness of its users, expressed in scarce commenting and posting activities. It could be partly explained as a typical behaviour of users at the early stages of blog existence. However, it was also consistent with the results of previous research of the librarianship blog, indicating the low activeness of users. It was concluded that the novelty of blogs as media and the emerging blog communication culture may be pre-requisites of the slow integration of this technology into professional communication practices. Finally, the value of the blog for researching professional communication issues was identified; however, it is still absent in library and information science publications.